The randon house writing course for esl students - Castello, Jacqueline; Tucker, Amy (New York: Rondom House, 1985)
Contents: 1.Loaking into language. 2.Making sentences. 3.How to write a how -to essay. 4. Setting the scenne. 5.Describing people. 6.Writting and revising the narrative essay. 7.Writing fables . 8.Definig, classifying,comparing, contrasting or four ways of looking at a computer. 9.Analyzing causes and effects. 10.Developing an argument.
Appendices p. 427-436. Index p. 437-442
Keywords: Conversation; English Language Texbooks